Medicolegal Autopsy Cases in Sivas 1990-1995 Demography and Properties of Forensic Medical Experts - Katkıcı, Ufuk (The Bulletin of Legal Medicine, 1997)
Demographic studies about medico-legal autopsies have been performed by means of the data from The Council of Forensic Medicine and it’s satellite offices in Turkey. In this study, we have investigated the autopsy archieves of Justice of Sivas. Demographic data have been evaluated and literature reviewed. Additionally, properties and qualifications of physicians who had performed autopsies and external examinations have been evaluated retrospectively. In this period 760 autopsies and external examinations had been performed. 541 of cases (71.2 %) had been evaluated with external examination and 219 of them with an autopsy (21.3 %)• The decedents were between the ages of 0-86, 72.9 % of them was male. The average of ages was; 34.5 ± 20.3 in male, 31.3 ± 22.6 in female. Deaths frequently were due to accidents (71.1 %), homicides (151 °/p), and suicides (6.4 %).Key words: Forensic autopsy, external examination, unnatural death, accident, homicide, suicide, forensic medical expertize.
Keywords: forensic autopsy; external examination; unnatural death; accident; homicide; suicide; forensic medical expertize